2020
DOI: 10.1093/jue/juaa023
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale assessment of Red-tailed Hawk reproductive success relative to urban density and habitat type

Abstract: Despite the unique threats to wildlife in urban areas, many raptors have established successfully reproducing urban populations. To identify variations in raptor breeding ecology within an urban area, we compared metrics of Red-tailed Hawk reproductive attempts to landscape characteristics in Reno and Sparks, NV, USA during the 2015 and 2016 breeding seasons. We used the Apparent Nesting Success and logistic exposure methods to measure nesting success of the Red-tailed Hawks. We used generalized linear models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Here, we did not investigate food supplementation effects on small urban fragments because several studies found that mortality exceeded recruitment in urban areas due to a variety of other factors (Bowman & Woolfenden, 2001 ; Breininger, 1999 ; Mumme et al, 2000 ). We assume Florida scrub‐jay sustainability depends on the degree of habitat fragmentation; generally broad conclusions about edge effects and fragmentation levels need further replication and quantification across circumstances and species (de Satgé et al, 2019 ; Frantz et al, 2018 ; Stephens et al, 2004 ; White et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we did not investigate food supplementation effects on small urban fragments because several studies found that mortality exceeded recruitment in urban areas due to a variety of other factors (Bowman & Woolfenden, 2001 ; Breininger, 1999 ; Mumme et al, 2000 ). We assume Florida scrub‐jay sustainability depends on the degree of habitat fragmentation; generally broad conclusions about edge effects and fragmentation levels need further replication and quantification across circumstances and species (de Satgé et al, 2019 ; Frantz et al, 2018 ; Stephens et al, 2004 ; White et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We assume Florida scrub-jay sustainability depends on the degree of habitat fragmentation; generally broad conclusions about edge effects and fragmentation levels need further replication and quantification across circumstances and species (de Satgé et al, 2019;Frantz et al, 2018;Stephens et al, 2004;White et al, 2020).…”
Section: Other Fecundity Differences Among Populationsmentioning
confidence: 99%
“…We then averaged the two periods and created an interpolated, continuous noise surface (range: 29–79.97 dB). Noise sampling locations were distributed throughout the urban gradient and were based on nest locations used in other urban‐avian guild research (White et al, 2020). We also acquired nighttime light emittance for each nest site captured by the Visible Infrared Imaging Radiometer Suite satellite dataset (750 m resolution).…”
Section: Methodsmentioning
confidence: 99%